Inclusive purchasing and supply chain resilience capabilities: Lessons for social sustainability. Issue 5 (December 2022) - Silva, Minelle E.; Ruel, Salomée
Abstract: In the face of unexpected changes in their dynamic business environment, purchasing and supply chain (SC) managers have been challenged to boost SC resilience while maintaining their sustainability concerns. In this changing environment, this paper aims to explore: (1) how (social) sustainability affects SC resilience and (2) what the role of purchasing is for SC resilience. Through a dynamic capability view as the theoretical lens, we investigate whether and how an inclusive purchasing programme could enhance SC resilience capabilities to cope with the Covid-19 outbreak. We developed a Case study with various SC members of a multinational cosmetics company that, despite suffering from a sudden demand disruption during the outbreak, maintained its sustainability actions. The results show that four operational SC resilience capabilities were amplified: 'visibility', 'adaptability', 'collaboration' and 'financial strength'. In addition, a new capability entitled 'empowerment' was mobilised during this period. These factors helped the inclusive purchasing maintenance and were essential to supporting social sustainability. In addition, our results show that sustainable PSM, which is overlooked in the literature, is key for SC resilience. This article contributes to theory and practice because it demonstrates the role and relevance of (inclusive) purchasing in a company's ability to cope with SC disruptions, such as those resulting from the outbreak. Highlights: Inclusive purchasing relies on multiple capabilities for social sustainability. Five capabilities were mobilised to cope with the Covid-19 outbreak. These capabilities are: visibility, adaptability, collaboration, financial strength and empowerment. Sustainable purchasing and supply management (PSM) plays a key role in supply chain resilience.